PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN TERHADAP KINERJA PEGAWAI PADA PUSKESMAS UJUNG JAMPEA KABUPATEN KEPULAUAN SELAYAR - Maurifah Maysarah; Nurman; M. Ikhwan Maulana Haeruddin; Siti Hasbiah; Uhud Darmawan Natsir (Lafadz Jaya Publisher, 2023)
Influence of Leadership Style and Commitment to Employee Performance at Ujung Jampea Health Center Selayar Islands Regency. Thesis. Management Study Program. Faculty of Economics and Business. Makassar State University. Supervised by Nurman and M. Ikhwan Maulana Haeruddin. This study aims to determine the influence of leadership style and commitment to employee performance. This research was conducted at the Ujung Jampea Health Center Selayar Islands Regency with a sample of 53 people consisting of employees at the Ujung Jampea Health Center Selayar Islands Regency. Data collection was carried out using the method of observation, interviews, questionnaires, and documentation. The data analysis technique used is multiple regression analysis using the Statistical Product and Service Solution (SPSS). The results of this study indicate that the t-test (partial) shows that leadership style (X1) has a positive and partially significant effect on employee performance (Y) with a significance value of 0.020, less than 0.05. Furthermore, commitment (X2) has a partially positive and significant effect on employee performance (Y) with a significance value of 0.027 less than 0.05. While the f (simultaneous) test results show that leadership style (X1) and commitment (X2) have a positive and significant simultaneous (together) effect on employee performance (Y) with a significance value of 0.002 less than 0.05. Furthermore, the coefficient of determination test (R²) shows an R Square value of 0.218 which means leadership style (X1) and commitment (X2) have an influence on employee performance variable (Y) of 21.8% while the remaining 78.2% is influenced by other factors in outside the independent variables in this study.